Digital Native in the Frame of Distant Learning during Covid-19 Pandemic Era - Herawati, Yayuk Widyastuti (MultiTech Publisher, 2023)
We could not forget the educational system when covid-19 outbreak in 2019 till 2021. At that time, we were forced to do everything at home including to study. The school system was changed totally. Related to that occurrence, the researcher did a survey to the third semester -students of tertiary level. The sample was three classes of 20 students each. The data was taken when the covid-19 occurred in 2020. At least, there were benefit, challenges, and strategies we could discuss in this study which need to address. This research contributes valuable insights into the intersection of digital natives and distant learning during the COVID-19 pandemic. Findings will inform educational institutions, policymakers, and educators on how to tailor distant learning approaches to better accommodate the needs and strengths of digital native students. The study may face limitations related to generalizability, as findings may be context-specific. Additionally, self-reporting bias is a potential challenge in survey responses.